Public Debt and Economic Growth - Greiner, Alfred; Fincke, Bettina (Dynamic Modeling and Econometrics in Economics and Finance, 2009)
Starting point of this book is the observation that an increase in public debt must be accompanied by a rise in the primary surplus of the government to guarantee sustainability of public debt. The book first elaborates on that principle from a theoretical point of view and then tests whether empirical evidence for that rule can be found. Additional tests are implemented to gain further evidence on sustainability of public debt. In order to allow for time varying coefficients penalized spline estimations are performed. The theoretical chapters present endogenous growth models and assume that the primary surplus rises as public debt increases so that sustainability of public debt is given. Implications of public deficits and debt are studied assuming full employment and for unemployment. The conclusion summarizes the findings and compares the results of the different models. Finally, policy implications are given showing how governments should deal with high public debt to GDP ratios.